Introduction of Tropical Pines in Orissa - Das, B. L. (Indian Forester, 1971)
Orissa is in a state of rapid industrializations and forest based industries play an important role in the State's economy as also the economy of the whole country. Tropical pines as a source of raw material are not only suitable but also offer multipurpose industrial use. Hence the necessity of their introduction in the State. The various tropical pines and other conifers that have hence introduced in the State and the State and the measure of success achieved in each case is described in detail in this article.